Beyond size: The potential of a geometric morphometric analysis of shape and form for the assessment of sex in hand stencils in rock art. (February 2017) - Nelson, Emma; Hall, Jason; Randolph-Quinney, Patrick; Sinclair, Anthony
Abstract: Hand stencils are some of the most enduring images in Upper Palaeolithic rock art sites across the world; the earliest have been dated to over 40 Kya in Sulawesi and 37 Kya in Europe. The analysis of these marks may permit us to know more about who was involved in the making the of prehistoric images as well as expanding the literature on the evolution of human behaviour. A number of researchers have previously attempted to identify the sex of the makers of Upper Palaeolithic hand stencils using methods based on hand size and digit length ratios obtained from digital or photo-based images of modern reference samples. Some analyses report that it was males who were responsible for the majority of hand stencils, whilst the most recent analysis determined that females produced the majority of hand stencils. Taken together, however, these studies generate contrasting and incompatible interpretations. In this study we critically review where we currently stand with methods of sexing the makers of hand stencils and the problems for the interpretation of hand markings of Palaeolithic age. We then present the results of a new method of predicting the sex of individuals from their hand stencils using a geometric morphometric approach that detects sexual differences in hand shape and hand form (size and shape). The method has the additional advantage of being able to detect these differences in both complete, as well as partial hand stencils. Finally we urge researchers to test this method on other ethnic groups and populations and consider ways of combining efforts towards a common goal of developing a robust, predictive methodology based on diverse modern samples before it is applied to Upper Palaeolithic hand stencils. Highlights: Geometric morphometric techniques were used to assess the sex of the makers of hand stencils. Using the form of the stencil, we were able to correctly predict sex in over 90% of our sample. The form of the palm is particularly sexually dimorphic and may help us predict sex from stencils with missing digits. Researchers should collaborate to develop methods of sex-prediction in living populations before analysing ancient images.